2012
DOI: 10.1111/j.1365-2958.2012.08074.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of intracytoplasmic membrane development in Rhodobacter sphaeroides

Abstract: SummaryThe purple phototrophic bacteria elaborate a specialized intracytoplasmic membrane (ICM) system for the conversion of solar energy to ATP. Previous radiolabelling and ultrastructural experiments have shown that ICM assembly in Rhodobacter sphaeroides is initiated at indentations of the cytoplasmic membrane, termed UPB. Here, we report proteomic analyses of precursor (UPB) and mature (ICM) fractions. Qualitative data identified 387 proteins, only 43 of which were found in the ICM, reflecting its speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…sphaeroides membranes has recently been reported [37] in which 43 unique proteins were identified in the highly specialized chromatophore membrane as compared to 236 making up the more complex membrane components isolated in the UPB fraction. A meatabolically stable isotope labeling procedure permitted determination of the relative distribution of proteins between the chromatophores and the UPB, revealing that the UPB is enriched in enzymes of lipid and tetrapyrrole biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…sphaeroides membranes has recently been reported [37] in which 43 unique proteins were identified in the highly specialized chromatophore membrane as compared to 236 making up the more complex membrane components isolated in the UPB fraction. A meatabolically stable isotope labeling procedure permitted determination of the relative distribution of proteins between the chromatophores and the UPB, revealing that the UPB is enriched in enzymes of lipid and tetrapyrrole biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Early chromatophore models prior to (Cartron et al, 2014) account only for LH proteins, whereas in proteomics studies, hundreds of different types of non-LH peptides are actually identified, including ATP synthase, cytbc 1 , membrane assembly factors, as well as proteins of unknown function (Jackson et al, 2012;Woronowicz and Niederman, 2010). Most of these components are notably unresolved in AFM images.…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptmentioning
confidence: 99%
“…sphaeroides the basic photosynthetic unit is the chromatophore (Cogdell et al, 2006;Strümpfer et al, 2011;Cartron et al, 2014), a 50-70 nm diameter vesicle, as shown in Figure 1, formed through invagination of the intracytoplasmic membrane (Tucker et al, 2010;Gubellini et al, 2007) and comprising over a hundred protein complexes (Jackson et al, 2012;Woronowicz and Niederman, 2010;Woronowicz et al, 2013). The proteins that constitute the chromatophore are primarily the light harvesting (LH) complexes, photosynthetic reaction centers (RCs), cytbc 1 complexes, and ATP synthases, which cooperate to harvest light energy for photophosphorylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect different degradation rates for the LH2 and RC-LH1 complexes, arising from a preferential protection of the cores from proteolysis. Alternatively, LH1 may be formed from accumulated polypeptide pools identified in the quantitative proteomics studies of Jackson et al [2012], as well as chromophores that may be directed toward LH1 rather than LH2 assembly. Surprisingly, fluorescence induction/relaxation measurements revealed that considerable photosynthetic activities were retained after transfer to oxic conditions (online suppl.…”
Section: Studies Of Transition From Photoheterotrophic To Chemoheteromentioning
confidence: 99%